Studies on the molecular level changes and potential resistance mechanism of Coreius guichenoti under temperature stimulation - Duan, Yuanliang; Li, Qiang; Zhou, Jian; Zhao, Han; Zhao, Zhongmeng; Wang, Lanmei; Luo, Mingkun; Du, Jun; Dong, Zaijie (Frontiers in Genetics, 2022)
In this study, we used transcriptome and proteome technology to analyze molecular level changes in tissues of Coreius guichenoti cultured at high temperature (HT) and low temperature (LT). We also screened for specific anti-stress genes and proteins and evaluated the relationships between them. We identified 201,803 unigenes and 10,623 proteins. Compared with the normal temperature (NT), 408 genes and 1,204 proteins were up- or down-regulated in brain tissues, respectively, at HT, and the numbers were 8 and 149 at LT. In gill tissues, the numbers were 101 and 1,745 at HT and 27 and 511 at LT. In gill tissues at both temperatures, the degree of down-regulation (average, HT 204.67-fold, LT 443.13-fold) was much greater than that of up-regulation (average, HT 28.69-fold, LT 17.68-fold). The protein expression in brain (average, up 52.67-fold, down 13.54-fold) and gill (average, up 73.02-fold, down 12.92-fold) tissues increased more at HT than at LT. The protein expression in brain (up 3.77-fold, down 4.79-fold) tissues decreased more at LT than at HT, whereas the protein expression in gill (up 8.64-fold, down 4.35-fold) tissues was up-regulated more at LT than at HT. At HT, brain tissues were mainly enriched in pathways related to metabolism and DNA repair; at LT, they were mainly enriched in cancer-related pathways. At both temperatures, gill tissues were mainly enriched in pathways related to cell proliferation, apoptosis, immunity, and inflammation. Additionally, Kyoto Encyclopedia of Genes and Genomes pathway analysis showed more differentially expressed proteins in gill tissues than in brain tissues at HT and LT, and temperature stimulation led to the strengthening of metabolic pathways in both tissues. Of the 96 genes we identified as potentially being highly related to temperature stress (59 from transcriptome and 38 from proteome data), we detected heat shock protein 70 in both the transcriptome and proteome. Our results improved our understanding of the differential relationship between gene expression and protein expression in C. guichenoti. Identifying important temperature stress genes will help lay a foundation for cultivating C. guichenoti, and even other fish species, that are resistant to HT or LT.